Alopecia universalis: a patient's perspective of the cumulative life course impairment. (1st October 2021) - Burns, L. J.; Flanagan, K. E.; Pathoulas, J. T.; Ellison, A.; Mesinkovska, N.; Senna, M. M.
Abstract: Click here for the corresponding questions to this CME article.